Dynamics of serological responses to defined recombinant proteins during Schistosoma mansoni infection in mice before and after the treatment with praziquantel - Eman Sayed Mohammed; Risa Nakamura; Yombo DJ Kalenda; Sharmina Deloer; Taeko Moriyasu; Mio Tanaka; Yoshito Fujii; Satoshi Kaneko; Kenji Hirayama; Ahmed I. Ibrahim; Mahmoud A. El-Seify; Asmaa M. Metwally; et al. (Public Library of Science (PLoS), 2020)
To eliminate schistosomiasis, appropriate diagnostic tests are required to monitor its prevalence and transmission, especially in the settings with low endemicity resulting from the consecutive mass drug administration. Antibodies that react with either crude soluble schistosome egg antigens or soluble worm antigen preparations have been used to monitor infection in low-prevalence regions. However, these detection methods cannot discriminate current and past infections and are cross-reactive with other parasites because both antigens contain numerous proteins and glycans from schistosomes, and standard preparations need maintenance of the life cycle of the schistosome. To evaluate the potential utility of nine recombinant Schistosoma mansoni proteins as single defined antigens for serological diagnosis, we monitored the kinetics of antibodies to each antigen during S. mansoni infection in mice before and after the treatment with praziquantel. C57BL/6 mice were infected with 50 cercariae. The levels of immunoglobulin G (IgG) raised against five recombinant antigens (RP26, sm31, sm32, GST, and LAP1) significantly increased as early as 2-4 weeks after infection and rapidly declined by 2 weeks after the treatment, whereas those raised against crude S. mansoni egg antigens or other antigens remained elevated long after the treatment. The IgG1 raised against RP26, sm31, and serpin decreased after the treatment with praziquantel, whereas the IgE raised against serpin declined strikingly after the treatment. This study clarifies the dynamics of the serological responses to recombinant S. mansoni proteins during infection and after the treatment with praziquantel and identifies several candidate antigens with potential utility in the monitoring and surveillance of schistosomiasis toward the elimination of schistosomiasis. Author summary Schistosomiasis is the second most important human parasitic disease in tropical and subtropical areas: estimates show that at least 218 million people required treatment in 2015 and remains a major Neglected Tropical Disease impacting the health of the poorest populations. The global strategy for schistosomiasis control is focused on eliminating disease through periodic, large-scale population treatment with praziquantel (PZQ). With the progress towards the control and the elimination of schistosomiasis by mass drug administration (MDA) with PZQ, more sensitive diagnostics that can monitor the dynamics of schistosomiasis transmission are required to instruct MDA programs and assess reinfection. Detecting antibodies react with either crude soluble schistosome egg antigens or soluble worm antigen preparations have been used to monitor infection in low-prevalence settings. However, these detection methods cannot discriminate current and past infections and are cross-reactive with other parasites because it contains numerous proteins and glycans from schistosomes, and standard preparations need maintenance of the life cycle of the schistosome. This study clarified that the dynamics of the serological responses to defined recombinant proteins during S. mansoni infection in mice before and after the treatment with PZQ and identifies several candidate antigens with potential utility in the monitoring and surveillance of schistosomiasis toward the elimination of schistosomiasis.